Entrepreneurship Training and Application of Break Even Point Analysis in the Framework of Generating an Entrepreneurial Spirit and Exploring New Ideas in Wearnes Malang Students - Yuniar Fitriyani; Tin Agustina Karnawati; Murtianingsih (Jurnal Pengabdian Masyarakat Formosa, 2022)
Wearnes is an out-of-school educational institution that provides computer, business and sales marketing materials with the aim of providing students with the skills to become entrepreneurs. However, the development and discovery of new ideas for entrepreneurship in educational institutions is still not optimal because the number of meetings on sales marketing material is relatively short, resulting in a lack of implementation of business/business concepts into business practices. For this reason, it is necessary to provide training to foster enthusiasm, new ideas and entrepreneurial creativity. This training also provides a way of calculating break even point analysis of the business plan that will be implemented, especially how to determine the selling price of its business products. The importance of providing this training is to contribute to students who are the younger generation with great potential to start new businesses and develop them in the future so that they have a large multiplier effect in creating new jobs.